Impact of COVID-19 pandemic on dermatology practice in India - Shashank Bhargava; Rashmi Sarkar (Wolters Kluwer Medknow Publications, 2020)
Background: COVID-19 pandemic has disrupted healthcare systems throughout the globe. It has affected dermatology practice to a great extent. Since most of the consultations (except emergencies) in dermatology are deferred as a precautionary measure, dermatologists have taken the route of virtual appointments in order to continue treating patients in the present lockdown state. However, the concept of telemedicine is quite new for doctors as well as for patients in India. Material and Methods: An online questionnaire was circulated among Indian dermatologists which included participant demographics, changes in their practice and teaching during COVID-19, use of virtual or e-health technologies, and attitudes/opinions on their experiences. We also wanted to understand doctor perspectives on their own roles, wellness, and hospital responses to the pandemic. Results: A total of 260 responses from qualified dermatologists of different parts of India were received between 1st and 8th April 2020 and were analyzed. Two-thirds of the respondents were within 10 years of starting practice. Virtual consultations have increased by almost three-fold during the pandemic, which is a major change noticed in the practice when we compare before and during the pandemic. Earlier the focus of teledermatology (TD) was mainly for follow-up care (85%), whereas during the pandemic, both new and follow-up patients were provided virtual consultations. The number of patients coming to them for a consultation has drastically reduced. Only 2% of the responders are still performing minor procedures with proper care. Almost two-thirds do not have systems in place to train their residents and fellows due to the disruptions caused by the pandemic. The rest of them have started to take the virtual route of teaching through webinars, virtual rounds, and providing access to online journals to continue their teaching. Only 18.6% of dermatologists at work were provided with personal protective equipment. TD has opened new doors to virtual consultation and it was evident that 54.4% of doctors are willing to continue it in the future even after the pandemic is over. Conclusion: TD platforms hold great promise to improve access to high-quality dermatologic care in the future. Results from this survey of Indian dermatologists suggest that TD is the future of dermatology as it will be accessed by patients in remote areas and it is a cost-effective move for the patients.